Fish Trader Behavior of Fish Market Mentaya Kota Sampit Based on The Principles of Islamic Business Ethics - Maulana, Satriya; El Wafa, Faqih; Faridah, Faridah (Lembaga Penerbitan Jurnal Ilmiah Institut Agama Islam Bani Fattah Jombang, 2024)
This research is motivated by behavior that does not follow Islamic business ethics principles based on initial observations made by the author through interviews with two fish merchants. The purpose of this study is to find out how the behavior of fish traders and the application of Islamic business ethics to the conduct of fish merchants at Mentaya fish market, Sampit City. This research is field research, with the subject being fish merchants who sell on fishing boats in the Mentaya Fish Market, Sampit City, totaling ten informants. The analysis used in presenting and compiling the data is descriptive qualitative analysis. Based on the results of this study: First, the Islamic business ethics behavior of 10 fish traders at the Mentaya fish market in Sampit City can be seen from several behaviors such as Free Will, Responsibility/Trust, Honesty, and Delivering. All traders apply these behaviors. Meanwhile, according to the conduct of Tauhid/Unity, only 4 out of 10 fish merchants have implemented this behavior, and for Fair behavior, 8 out of 10 traders have implemented this behavior. Second, judging from the application of Islamic business ethics to the conduct of fish merchants at the Mentaya fish market, Sampit City, who has implemented Islamic business ethics behavior as a whole, from 10 informants, only two people, or about 20%.